Is received dose from ingested soil independent of soil PAH concentrations?—Animal model results. (13th June 2016) - Peters, Rachel E.; James, Kyle; Cave, Mark; Wickstrom, Mark; Siciliano, Steven D.
Abstract: Polycyclic aromatic hydrocarbon (PAH) bioavailability from ingested soils will vary between soils; however, the nature of this variation is not well characterized. A juvenile swine model was used to link external exposure to internal benzo[ a ]pyrene (BaP) and anthracene exposure following oral PAH ingestion of 27 different impacted site soils, soots, or spiked artificial soils. Internal exposure of BaP and anthracene, represented by area under the plasma‐time curve, did not relate to soil concentration in impacted site soils, but did relate in spiked artificial soil. Point of departure modeling identified soil PAH concentrations greater than 1900 mg kg −1 as the point where area under the curve becomes proportional to external dose. A BaP internal exposure below 1900 mg kg −1 had an upper 95% confidence interval estimate of 33% of external exposure. Weak relationships between soil:simulated gastrointestinal fluid PAH partitioning and area under the curve values suggest that differences in internal PAH exposure between soils may not be dominated by differences in PAH partitioning. The data seem to best support exposure assessment assuming constant internal PAH exposure below soil concentrations of 1900 mg kg −1 . However, because constant internal exposure would challenge several existing paradigms, a bioavailability estimate of 33% of the external exposure is suggested as a likely workable solution. Environ Toxicol Chem 2016;35:2261–2269. © 2016 SETAC